TICKET QUEUE SERVICES AT DR. SOETOMO SURABAYA, A PHENOMENA - Yurilla Endah Muliatie; Sri Suprapti; Nur Jannah (SEAN Institute, 2023)
RSUD Dr. Soetomo is a government-owned hospital in East Java Province located in the city of Surabaya, which is one of the largest hospitals in Indonesia. As a type A hospital, hospital patients come from various regions and even from outside the island to East Indonesia. Due to the large number of patients who mostly use BPJS, the queue at the BPJS counter can reach hundreds of people per day. Even though the hospital has provided online services and several other conveniences, there are one thing or another that causes patients to have to queue manually. This is what makes the BPJS counter queue service appear. Even though it operates secretly, many patients use the services of these ticket queue service providers. This business is promising because the patients who go to RSUD Dr. Soetomo has to have regular check-ups every month and this can take years until they are declared cured. From the interview results it can be seen that these ticket queue service providers carry out their activities because they feel sorry for the patients and their families who have to queue from dawn to get BPJS tickets. The conclusion that can be drawn from this research is that with the service quality provided by these ticket queue service providers, they get free promotion by word of mouth so that many patients who need their services do not have to think long about using them.